Salafi, Hadith, and Islamic Law: Identity Politics and Wahabi Movement in East Kalimantan - Abdul Majid; Mahdalena Nasrun; Novizal Wendry; Ruslan Sangaji; Abdul Hakim (Universitas Islam Negeri Jakarta, 2023)
This study explores the Salafi-Wahabi movement's typology of hadith understanding and its consequences for Islamic law. This qualitative study employs the identity politics theory and the hadith understanding theory. Identity politics is utilized to assess the Salafi movement, and the concept of hadith understanding is used to examine different understandings of hadith. This study found that Salafi developed as a response to the behavior of bid’ah (innovation in religion), currents of syncretism, pluralism, liberalism, and the legitimating influence of Shia. The Salafi believes that Islamic organizations in Indonesia have failed to respond and have even been dissolved by the current situation, leading Muslims to stray away from hadith. Their identity politics is defined through numerous projects, including returning to Quran and sunnah slogans, putting on robes (long garments for both men and women), beards, and kuniyah. This is a way for them to justify their existence to oppose conventional identities. This study contends that the Salafi group's textual understanding of hadith promotes rigid Islamic law, which leads to societal conflict. As a result, the government and religious institutions should work together to develop Washatiyah Islam as a counter-ideology and discourse. Abstrak: Kajian ini bertujuan untuk membahas tipologi pemahaman hadis kelompok Salafi-Wahabi dan implikasinya pada hukum Islam. Studi ini merupakan penelitian kualitatif dengan menggunakan teori politik identitas dan teori pemahaman hadis. Politik identitas digunakan untuk menganalisis Salafi sebagai sebuah gerakan, sedangan teori pemahaman hadis menganalisis varian pemahaman hadisnya. Artikel ini menyimpulkan bahwa kelompok Salafi berkembang akibat reaksi mereka terhadap perilaku bid'ah, sinkretisme, pluralisme, liberalisme dan pengaruh Syiah. Bagi mereka, organisasi Islam yang mainstrem di Indonesia gagal merespons bahkan ikut larut oleh arus tersebut sehingga umat Islam semakin jauh dari hadis. Politik identitas mereka diartikulasikan dengan berbagai proyek, yaitu kembali kepada al-Quran dan sunnah, pakaian gamis, jenggot dan penggunaan kuniyah. Hal ini merupa- kan cara untuk melegitimasi eksistensi mereka guna meresistensi identitas mainstream. Penelitian ini beragumen bahwa pemahaman hadis kelompok Salafi yang tekstual melahirkan hukum Islam yang kaku dan mengakibatkan konflik sosial. Karena itu, pemerintah dan organisasi keagamaan hendaknya mengembangkan Islam washatiyah sebagai kontra ideologi dan wacana.